Micro-Valences: Perceiving Affective Valence in Everyday Objects - Lebrecht, Sophie; Bar, Moshe; Barrett, Lisa F.; Tarr, Michael J. (Frontiers in Psychology, 2012)
Affective valence influences both our cognition and our perception of the world. Indeed, the speed and quality with which we recognize objects in a visual scene can vary dramatically depending on its affective content. However, affective processing of visual objects has been typically studied using only stimuli with strong affective valences (e.g., guns or roses). Here we explore whether affective valence must be strong or obvious to exert an effect on our perception. We conclude that the majority of objects carry some affective valence (“micro-valences”) and, thus, nominally “neutral” objects are not really neutral. Functionally, the perception of valence in everyday objects facilitates perceptually-driven choice behavior, decision-making, and affective responses.